Pemanfaatan E-Filing sebagai Solusi dan Tantangan Pelaporan SPT Wajib Pajak Orang Pribadi di KPP Pratama Magelang - Fitria Dita Kurniasari; Bayu Kurniawan (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine the experience of Individual Taxpayers in using the e-Filing system at the Tax Service Office (KPP) Pratama Magelang, as well as identify the obstacles faced and solutions that can be applied to improve the effectiveness of reporting Annual Tax Return (SPT) electronically. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation of three informants who were purposively selected based on certain criteria. The results show that although e-Filing offers easy access and time efficiency, its implementation still encounters various obstacles, such as low digital literacy, technical constraints, and lack of confidence in using the system. Some informants still choose to report their tax returns directly to the Tax Office because they feel more comfortable with face-to-face assistance. These findings indicate that the successful implementation of e-Filing is highly dependent on adequate educational support, responsive technical services, and supportive infrastructure. This study recommends the need for continuous improvement in the quality of tax education, personalised assistance, and strengthening of technological infrastructure. Through an inclusive and adaptive approach, e-Filing is expected to function as a strategic instrument in building a culture of tax compliance based on convenience, awareness, and public trust in the digital taxation system.